From the Distinction between Palatalized and Palatal Consonants to the Distinction between Palatalizations and Palatations of Velar Consonants in the Proto-Slavic Language - Яковлевич Бурмистрович, Юрий (Slavistica Vilnensis, 2009)
The article explores two phonetic phenomena: palatation and palatalization. Taking into consideration the contribution made by V. Chekman and Kalleman toward the understanding of these phenomena, the article provides a thorough analysis of the processes and outcomes of the first, second, and third Common Slavic palatalizations of velar consonants.